2015
DOI: 10.1016/j.psep.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and reduced-scale experimental investigation of blast wave shape in underground transportation infrastructure

Abstract: When an explosion occurs in a tunnel, the study of the blast wave quickly becomes complicated, owing to the multiple propagation patterns of the blast wave (Incident wave, regular and Mach reections) and to the geometrical conditions. Considering this problem, two patterns can be revealed. Near the explosive, the well known freeeld pressure wave can be observed. After multiple reections on the tunnel's walls, this overpressure behaves like a one-dimensional (1D) wave. One aim of this paper is to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Benselama [12] and Uystepruyst [13] proposed two ways of the evolution of blast wave in tunnels and simulated the propagation of subway blast wave in tunnels through numerical calculation. The model test and simulation results were roughly consistent [14]. Smith [15] established a multigroup tunnel model and investigated the effect of tunnel wall roughness on shock wave attenuation.…”
Section: State Of the Artmentioning
confidence: 60%
“…Benselama [12] and Uystepruyst [13] proposed two ways of the evolution of blast wave in tunnels and simulated the propagation of subway blast wave in tunnels through numerical calculation. The model test and simulation results were roughly consistent [14]. Smith [15] established a multigroup tunnel model and investigated the effect of tunnel wall roughness on shock wave attenuation.…”
Section: State Of the Artmentioning
confidence: 60%
“…ey proposed a correlation law by a numerical study to define the transition distance according to the explosive charge and the geometry of the propagating domain. Pennetier et al [26] conducted a scaled model test and numerical simulation of blast waves in tunnels and found that the data of the experimental tests fit well with the numerical simulation. In field tests, Rodríguez et al [6,27] developed a semiempirical model to predict the air wave pressure and sound level outside a tunnel due to the blasting inside.…”
Section: Introductionmentioning
confidence: 96%
“…Xing et al [11] revealed complex influences of goaf with different caved areas on the velocity and pressure of the air shock wave in different mining faces. Pennetier et al [12] performed experiments of the air shock flushed the tunnel and presented evolution of the pressures and velocities of both the inlet and outlet tunnel in detail with the measurements on different blasted volume. Moreover, the test instruments used in experiments were not the same, such as thermal anemometer [13], different-pressure anemometer [14], ultrasonic anemometer [15].…”
Section: Introductionmentioning
confidence: 99%